Peran NGO dalam Memberdayakan Relawan (Studi pada Instagram @involuntirsurabaya) - Regita A. Benitis; Muhammad Jacky (Paradigma, 2025)
This research examines the practice of volunteer empowerment by non-governmental organizations (NGOs), particularly Involuntir Surabaya, which operates predominantly through the digital media Instagram @involuntirsurabaya. By employing an online qualitative approach and considering Critical Hacking Analysis (CrHA) as a methodological approach, supported by Platform Resistance Analysis (PRA), this study focuses on digital interactions observed on the @involuntirsurabaya Instagram platform as the primary data source. The research is grounded in Jim Ife’s theory as a grand theory discussing capacity building and social justice, complemented by Anthony Giddens’ Structuration Theory to understand the relationship between agents and structures in the digital space, as well as Participatory Action Research (PAR) and Community-Based Participatory Research (CBPR) as models of empowerment internalized in NGO practices. The main findings of the research identify innovative and digitally-based volunteer recruitment patterns, the dynamics of social relations between NGOs and volunteers, and various empowerment practices formed and expressed through Instagram @involuntirsurabaya. This observation includes how NGOs strategically utilize Instagram features and algorithms to achieve empowerment and social mobilization goals in a digital context, thereby successfully building volunteer trust and attracting them to join activities whose entire promotion is done online. Keywords: Volunteer, Community Development, Non-Governmental Organization (NGO), Instagram.